Tuning Stoichiometry for Enhanced Spin‐Charge Interconversion in Transition Metal Oxides - Hetian Chen; Dingsong Jiang; Qinghua Zhang; Yuhan Liang; Jingchun Liu; Aihua Tang; Yahong Chai; Pu Yu; Tianxiang Nan; Di Yi (Advanced Electronic Materials, 2024)
Abstract Interconversion of spin and charge current provides a key route for low‐power spin memory and logic devices. Recent advances have revealed efficient spin‐charge interconversion in 4d and 5d transition metal oxides. However, the strategies to tune the conversion efficiency, essential for the generation and detection of spin‐current, are limited to engineering the crystalline structure of oxides. Here, a simple and broadly applicable approach by tuning the cation stoichiometry is reported. In the model system of 5d perovskite SrIrO3, it is shown that a significant Ir cation deficiency is induced by controlling the oxygen partial pressure during deposition. This off‐stoichiometry leads to an enhancement of the spin‐to‐charge conversion efficiency by around three times, accompanied by an increase of electrical resistivity at room temperature. Furthermore, a significant increase of inverse spin Hall voltage is observed by implementing the Ir‐deficient SrIr1‐xO3, highlighting the promising role of atomic defects in developing oxides for sensitive spin‐current detection. This work opens a new pathway to engineer the spin‐charge interconversion efficiency in oxides and offers new opportunities to integrate complex oxides in energy‐efficient spintronic devices.